The Wisdom in Virtue: Pursuit of Virtue Predicts Wise Reasoning About Personal Conflicts. (December 2017) - Huynh, Alex C.; Oakes, Harrison; Shay, Garrett R.; McGregor, Ian
Most people can reason relatively wisely about others' social conflicts, but often struggle to do so about their own (i.e., Solomon's paradox). We suggest that true wisdom should involve the ability to reason wisely about both others' and one's own social conflicts, and we investigated the pursuit of virtue as a construct that predicts this broader capacity for wisdom. Results across two studies support prior findings regarding Solomon's paradox: Participants ( N = 623) more strongly endorsed wise-reasoning strategies (e.g., intellectual humility, adopting an outsider's perspective) for resolving other people's social conflicts than for resolving their own. The pursuit of virtue (e.g., pursuing personal ideals and contributing to other people) moderated this effect of conflict type. In both studies, greater endorsement of the pursuit of virtue was associated with greater endorsement of wise-reasoning strategies for one's own personal conflicts; as a result, participants who highly endorsed the pursuit of virtue endorsed wise-reasoning strategies at similar levels for resolving their own social conflicts and resolving other people's social conflicts. Implications of these results and underlying mechanisms are explored and discussed.